Nutrient recycling through litter production from different multipurpose trees in agrisilviculture system under rainfed conditions of Gujarat - Desai, N.H.; Shakhela, R.R.; Bhatt, P.K. (Indian Journal of Agroforestry, 2020)
The present study was conducted to investigate the quantity of litter fall, return of nutrients and carbon sequestration by 15 years old trees in the agroforestry system. Five treatments viz. Azardirachta indica A. Juss (Neem), Ailanthus excelsa Roxb. (Ardusa), Hardwickia binata Roxb. (Anjan) and Dalbergia sissoo Roxb. (Shisham) intercropped with rainfed Vigna unguiculata (L.) walp. (cowpea), Vigna radiata R. wilczek (green gram), Cyamopsis tetragonoloba (L.) Taub. (cluster bean) and Sesamum indicum L. (til) under agrisilviculture system and open field were taken in randomized block design with three replications. Average litter fall production of three years (2009, 2010 and 2011) was significantly highest in A. excelsa (18.40 t ha-1yr-1) followed by A. indica (12.73 t ha-1 yr-1), D. sissoo (10.36 t ha-1 yr-1) and H. binata (8.60 t ha-1 yr-1). The maximum tree height (8.52 m), diameter at breast height (23.13 cm) and clear bole length (3.04 m) were recorded in A. excelsa. The nutrients content (N, P and K) were highest in the litter fall of A. indica and lowest in H. binata. A. excelsa showed highest rate of N, P and K addition through litter fall (185.80, 259.40 and 97.51 kg ha-1 , respectively). All the tree species increased organic carbon, organic matter and available nutrients in soil as compared to open crop field. Among all the tree species, A. excelsa and A. indica appeared to be the most efficient in capturing carbon and removal of CO2 from atmosphere, while D. sissoo and H. binata the least.